A Comparative Comment on the Case Studies - Christian Christrup Kjeldsen; Thomas Ley; Niels Rosendal Jensen; Hans-Uwe Otto (Social Work and Society)
This paper brings up some central aspects from the case studies and brings them briefly together within an analytical and heuristic framework of the capability approach. We argue that the Capabilities for Education, Work and Voice should be considered as the main fertile capabilities in the studied domain. These three theoretically and empirically driven concepts are addressed one by one. At the end we broaden this further with the awareness that these capabilities have to be understood in their relational dependencies, conditions and consequences as well as in relation to the contextual differences they operate within. Hence, the mentioned set of capabilities is regarded as an important relational frame that can"enable young people to act as capable citizens in European societies" (according to the WorkAble objective), and besides of that it can be used as an evaluative framework raising questions which social and institutional conditions are necessary for young adults.